Diagnostic Accuracy of C-Reactive Protein in Detecting Bronchopneumonia in Children, Taking CT Scan as the Gold Standard - Liaqat, Mahnoor; Qureshi, Aamer Naseer (Biological and Clinical Sciences Research Journal, 2025)
Bronchopneumonia remains a leading cause of morbidity and mortality among children, particularly in low- and middle-income countries. Timely and accurate diagnosis is crucial for early initiation of appropriate therapy. Although computed tomography (CT) of the chest is considered the reference standard for detecting bronchopneumonia, its routine use in children is limited due to radiation exposure and resource constraints. C-reactive protein (CRP), an acute-phase reactant, has emerged as a potential adjunct diagnostic biomarker; however, evidence regarding its diagnostic accuracy in pediatric bronchopneumonia from resource-limited settings remains limited. Objective: To determine the diagnostic accuracy of serum C-reactive protein in detecting bronchopneumonia in children, using a CT scan of the chest as the reference standard. Methods: A cross-sectional validation study was conducted in the Department of Paediatrics, Allied Hospital, Faisalabad, Pakistan, over six months from 10 April 2024 to 10 October 2024. Children aged 2 months to 12 years presenting with clinical features suggestive of bronchopneumonia were consecutively enrolled. Serum CRP levels were measured, and a cut-off value of ≥ 70 mg/L was used to define a positive test. All participants underwent a chest CT, which served as the reference standard for diagnosing bronchopneumonia. Diagnostic performance measures, including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), overall diagnostic accuracy, and likelihood ratios, were calculated using 2 × 2 contingency tables. Stratified analyses were performed to assess the effect of age and gender on diagnostic performance. Results: A total of 145 children were included, with a mean age of 3.8 ± 2.6 years; 59.3% were male. Bronchopneumonia was confirmed on CT scan in 61 children (42.1%). CRP demonstrated a sensitivity of 85.2% and specificity of 85.7% for detecting bronchopneumonia. The PPV and NPV were 81.3% and 88.9%, respectively, with an overall diagnostic accuracy of 85.5%. The positive likelihood ratio was 5.96, and the negative likelihood ratio was 0.17. Stratified analysis showed comparable diagnostic performance across age groups and genders. Conclusion: Serum CRP demonstrates good diagnostic accuracy for detecting bronchopneumonia in children compared with a CT. In resource-limited settings, CRP may serve as a valuable adjunct to clinical assessment, potentially reducing reliance on CT imaging and minimizing radiation exposure in pediatric patients.